A numerical analysis of NMR pore-pore exchange measurements using micro X-ray computed tomography - Melean, Y.; Washburn, Kathryn E.; Callaghan, P. T.; Arns, Christoph H. (Diffusion Fundamentals, 2009)
Pore-pore relaxation exchange experiments are a recent development and hold great promise to spectrally derive length scales and connectivity information relevant for transport in porous media. However, for large pores, NMR diffusion-relaxation techniques reach a limit because bulk relaxation becomes dominant. A combination of NMR and Xray-CT techniques could be beneficial and lead to better models for regions of unresolved porosity in CT images, increasing the accuracy of image based calculations of transport properties. In this study we carry out numerical NMR pore-pore exchange experiments on selected Xray-CT images of sandstones and carbonate rock, while at the same time tracking information about the geometry and topology of the pore space. We use pore partitioning techniques and geometric distance fields to relate T2-T2 relaxation exchange spectra to underlying structural quantities. It is shown that T2-T2 pore-pore exchange measurements at room temperatures for the samples considered likely reflect exchange between pores and throats or pores and roughness.